The new roles of Legon Botanical Garden as visitor destination in Ghana - Eric Cudjoe; Shine Francis Gbedemah (Goodwood Publishing, 2019)
Abstract Purpose: This study aims to examine the travel motivations and determine the most attractive facilities of visitors to the University of Ghana’s Legon botanical garden in Accra, Ghana. Research Methodology: The study relied on convenience sampling method to administer structured questionnaires to 127 visitors to the Legon botanical garden. Results: Findings show that the main reason for visiting the garden is to admire the beauty of the garden which is the main reason for establishing botanical gardens. The most attractive facility in the garden, however, turns out to be the canopy walkway and the lawn. Conspicuously missing is the fact that they did not avail themselves to enquire or demand to know tree species and their names in the garden. Limitations: The study is limited to only adults who visited the garden at the time of the study even though they are on the minority compared to children. Also, the study is limited only to the Legon botanical garden even though it is not the only garden in Ghana. Contribution: This study contributes to the knowledge in the social sciences by pointing out the most important reasons why people are visiting botanical gardens. This is because the number of visitors seems to be increasing in Ghana. However, the findings show that the visitors do not visit the garden for education, research or conservation purposes but for leisure activities which is not the main reason for establishing these gardens. Keywords: Botanical garden, Visitors, Motivation, Facilities, Ghana